2015
DOI: 10.1590/s0102-865020150110000008
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the areas of osteochondral defects produced in femoral condyles of rabbits treated with sugar cane biopolymer gel

Abstract: PURPOSE:To assess the histological response of damaged osteochondral tissue in the femoral condyles of rabbits after repairing the wounds with sugar cane biopolymer gel -compared to the control group. METHODS:The study investigated 16 New Zealand rabbits, at 90, 120 and 180 days after surgery. In all the animals, a lesion of 3.2 mm in diameter and 4 mm deep was induced in each right and left femoral condyle. Each animal has provided both knees, divided into medial and lateral condyle, resulting in 64 samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition to inflammation, it can be observed constant bone degeneration and osteophyte formation, seen in the radiographic images shown in this experiment. This model has served as the basis for experimental treatment of osteoarthritis in various ways [24][25][26] .…”
Section: Microscopic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inflammation, it can be observed constant bone degeneration and osteophyte formation, seen in the radiographic images shown in this experiment. This model has served as the basis for experimental treatment of osteoarthritis in various ways [24][25][26] .…”
Section: Microscopic Analysismentioning
confidence: 99%
“…The Roto-rod, although initially designed for forced ambulation on gait in lesions of the cerebellum 15 , is also used in the grading of joint function in experimental neurological compressions 27 , and joint changes in experimental arthritis of the knees 16,25 . This study showed that the greatest difference occurred in 7 and 14 days after induction.…”
Section: Control Group (Cg)mentioning
confidence: 99%
“…A study carried out addressing the cytotoxicity, genotoxicity and antigenotoxicity of BC when testing it in vitro and in vivo in rats, demonstrated that they are neither cytotoxic nor genotoxic [14,20], other studies also addressed the theme and proved BC biocompatibility and atoxicity [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, additional surgical is required to remove the non-degradable nerve conduits. For this reason, research in the last decade has intensified, in an attempt to analyze biocompatible materials and capable of bio-absorption for use as guide tubes for bridging to axonal growth (Albuquerque et al, 2015).…”
Section: Introductionmentioning
confidence: 99%